Patrimonio industrial en Magallanes - Valenzuela Blossin, Arq. Maria Paz (Universidad Nacional del Litoral, 2018)
Towards the end of the nineteenth century, the exploitation of sheep farming in Chile was consolidated, with the region of Magellan as its scene. In this way the vast southern territory is colonized by the sheep farms, installing a model of livestock exploitation equivalent to that of the whole planet supplying the industrialized world of raw materials for the production of textiles.The development of these processes along with what happened in the rest of the world caused the entrepreneurs of the sector to look for new derivations of sheep production, thus creating the refrigeration industry in Patagonia, which will provide services to all stays in the southern end of the continent, making own technology of the cold, budding in the world. Together with the unique architecture of both sets, there will be another contribution: the generation of complex industrial processes that exceed the single production of raw material, the refrigerators being a case of vanguard in the Chilean industrial area, which to date was characterized by the majority extraction and production of raw materials. Stations and cold storage industry will be the contribution of Magallanes to the industrialization in Chile.